Vibroacoustic behavior of a rectangular composite plate in thermal environment - Thinh, Tran Ich; Thanh, Pham Ngoc (Vietnam Journal of Mechanics, 2022)
This paper is a study of the vibroacoustic behavior of orthotropic laminated composite rectangular plate under a sound wave excitation in thermal environments. An improved analytical procedure has been developed that allows for an efficient solution of the finite composite plate sound transmission problem. A symmetrically orthotropic laminated composite plate is considered. The plate is modeled with classic thin-plate theory and is assumed to be clamped on all four sides. The incident acoustic pressure is modeled as a harmonic plane wave impinging on the plate at an arbitrary angle. The sound transmission loss is calculated from the ratio of incident to transmitted acoustic powers.